Transcriptomic and volatile organic compounds analysis of resistance mechanisms and diversity of late blight pathogen populations in the Baltic Sea region - Agho, Collins Aimuaenvbosa (Estonian University of Life Sciences, 2024)
A Thesis for applying for the degree of Doctor of Philosophy in Agriculture. Väitekiri filosoofiadoktori kraadi taotlemiseks põllumajanduse erialal. ABSTRACT. This thesis addressed in part the dynamics and diversity of late blight pathogen populations in unstudied regions (Estonia islands and Pskov region of north-western Russia) by understanding changes in the spatiotemporal variation of the P. infestans population structure, the prevalent reproduction mode, genotypic and phenotypic diversity and the impact of transboundary migration and gene flow on the P. infestans population (Paper I and II). Mating type determination, metalaxyl response and SSR marker genotyping of P. infestans isolates were used in the first and second experiments. Our result suggests a predominance of sexual reproduction that may have resulted in the observed high genotypic diversity and a high proportion (> 60%) of unique genotypes in these unstudied regions. Time-dependent changes in metalaxyl response and rapid changes in the pathogen populations with the absence of shared genotypes over the years were observed. Overall, there was a lack of genetic differentiation and an absence of local adaptation allowing for the exchange of genetic materials among the P. infestans populations of the Estonian islands and mainland Pskov region P. infestans populations, and between Estonian island and mainland Pskov regions populations. Secondly, the diversity of the chemical profile (volatile organic emission/VOC) of potato cultivars with variation in late blight resistance background was examined (Paper III). The result indicates the presence of qualitative and quantitative differences among the potato cultivars, and the dominance of terpenoids in the emission blend. The composition of sesquiterpenes was cultivar-specific. Interestingly, the VOC emission blend accounted for a high proportion of variation among the cultivars, and the total terpenoid and total constitutive VOC emission scale positively with resistance. The use of VOCs holds ...